1981
DOI: 10.1161/01.hyp.3.5.601
|View full text |Cite
|
Sign up to set email alerts
|

Micropressure-flow relationships in a skeletal muscle of spontaneously hypertensive rats.

Abstract: SUMMARY Direct intravital microscopy was used to analyze microclrculatory changes in the exteriorized spinotrapezius muscle of spontaneously hypertensive rats (SHR). The animals were anesthetized with a mixture of chloralose-urethane, and measurements made of pressure, flow, and resistance in vessels ranging in size from 50 to 5 Mm. Tbe vascular changes in SHR were compared with matched Wistar-Kyoto (WKY) strain animals for both young (5-6 weeks old) and mature (12-13 weeks) rats. Distinctive changes in tbe di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
3

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 37 publications
(15 reference statements)
5
81
3
Order By: Relevance
“…This discrepancy may reflect an interspecies difference in the relative importance of structural versus functional adjustments at the microvascular level during maturational changes in tissue metabolism. With the assumption that changes in arcade bridge volume flow accurately reflect changes in total network blood flow, the 25% volume flow increase from weanling to juvenile rats (Table 2) is consistent with previous reports of growth-related increases in total blood flow to rat spinotrapezius muscle (36) and rat cremaster muscle (33). However, from our recent finding that spinotrapezius muscle mass increases by almost 2.5-fold over this same period (19), blood flow per gram of tissue must actually decrease with growth.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This discrepancy may reflect an interspecies difference in the relative importance of structural versus functional adjustments at the microvascular level during maturational changes in tissue metabolism. With the assumption that changes in arcade bridge volume flow accurately reflect changes in total network blood flow, the 25% volume flow increase from weanling to juvenile rats (Table 2) is consistent with previous reports of growth-related increases in total blood flow to rat spinotrapezius muscle (36) and rat cremaster muscle (33). However, from our recent finding that spinotrapezius muscle mass increases by almost 2.5-fold over this same period (19), blood flow per gram of tissue must actually decrease with growth.…”
Section: Discussionsupporting
confidence: 88%
“…During juvenile growth, rapid increases in tissue mass are accompanied by extensive growth of the arteriolar, venular, and capillary networks (11,19,31,33) and by increases in microvascular pressure (36) and tissue blood flow (33,36). In light of these structural and hemodynamic changes, it is reasonable to expect an accompanying change in the functional relationship between endothelium and vascular smooth muscle.…”
mentioning
confidence: 99%
“…These results indicate that the smaller diameters of the renal preglomerular vasculature of young SHR vs normotensive rats are due to differences in active vascular tone rather than a structural narrowing of the vessels. Previous studies have demonstrated an increased cerebral vascular tone in young SHR, 19 and studies of the skeletal muscle microcirculation have shown an increased vascular resistance 20 -22 that was due, in part, to vascular rarefaction. 22 The present study is the first to observe directly an increase in active renal vascular tone as early as 4 weeks in the SHR.…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly important in the large arterioles, which contribute the major portion of the overall resistance of the vascular bed. Zweifach et al (51) showed that, in the rat spinotrapezius, ϳ60% of the pressure drop occurs before the transverse arterioles (diameter 8-30 m). Similar results have been observed in other tissues (7,35,48), although the distribution of resistances in larger, conscious animals has not been determined.…”
Section: Anatomical Evidence For Venular-arteriolar Communicationmentioning
confidence: 99%